Agricultural export and economic growth in ASEAN countries - KYAW, AYE MON MON (KDI School, 2017)
Many of developing countries in ASEAN community are still depend on the agricultural environment. This research applied the fixed effect and random effects regression model to examine the impact of the primary product of agricultural export on the countries economics growth in selected developing ASEAN countries. The study period is from 1995-2014 using year dummy variables. The outcomes of the study show the primary products of agricultural raw materials export is statistically significant on the inverse relation on the growth of economic. But the manufactured export (non-agricultural export) is strongly and positively effect on the economic development. Based on main finding of this research, this study concluded that the domestically value-added processing should be encouraged instead of exporting raw material to the foreign market. Over-reliance on primary agriculture export (raw material) may suffer economic development of the country. The manufactured export should expand to rapid increase of economic development.
Thesis(Master) --KDI School:Master of Public Policy,2017